1999
DOI: 10.1111/j.1532-5415.1999.tb01288.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Hyperactivity in Hypertensive Older Patients Is Controlled by Lowering Blood Pressure

Abstract: This study demonstrated that even in a population of older hypertensive patients with no other risk factor for atherogenic disease, normalization of blood pressure induces a significant reduction of the parameters of enhanced platelet hyperactivity independent of the action exerted, at the platelet level, by the antihypertensive drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…37 One study has found a nonsignificant reduction in soluble P-selectin with quinalapril and nifedipine. 38 The importance of our study is that we have demonstrated that in subjects at particularly high cardiovascular risk by virtue of having TOD, significant reductions in hemorheological, platelet, and endothelial markers (with the exception of fibrinogen) may be achieved by intensified BP control and risk factor management.…”
Section: Discussionmentioning
confidence: 99%
“…37 One study has found a nonsignificant reduction in soluble P-selectin with quinalapril and nifedipine. 38 The importance of our study is that we have demonstrated that in subjects at particularly high cardiovascular risk by virtue of having TOD, significant reductions in hemorheological, platelet, and endothelial markers (with the exception of fibrinogen) may be achieved by intensified BP control and risk factor management.…”
Section: Discussionmentioning
confidence: 99%
“…57 In addition to the impairment of vascular reactivity and permeability, other anti-atherosclerotic functions of nitric oxide are also diminished in hypertension, which may result in activated monocyte, leukocyte, and platelet adhesion to endothelium and increased platelet aggregation. 59,60 Calcium antagonists may increase endothelial nitric oxide bioavailability by several mechanisms. 61,62 Our results may be a reflection of the action of calcium antagonist on nitric oxide.…”
Section: Discussionmentioning
confidence: 99%
“…53 These components appear to be related to target organ damage, longterm prognosis and are altered by treatment. 53,54 Many studies have also demonstrated abnormalities in coagulation factors, platelets and the endothelium in patients with PVD, where they are predictive of adverse outcome. For example, elevated fibrin Ddimer levels, an index of thrombogenesis and fibrin turnover, 55 have been found in patients with PVD, which correlate with clinical, haemodynamic and angiographic severity.…”
Section: Pathophysiological Considerationsmentioning
confidence: 99%